CCBD's Position on Eliminating the Use of Seclusion in Educational Settings. (February 2023) - Freeman, Jennifer; Peterson, Reece; Kern, Lee; Mathur, Sarup R.; Barber, Brian; Power, Mara; Perea, Madison
This document provides recommendations of the Council for Children with Behavioral Disorders (CCBD) regarding the use of seclusion in schools. It updates the CCBD's position on this topic first published in 2009 and includes (a) key definitions, (b) a summary of problems with the use of seclusion, (c) strategies to eliminate the use of seclusion, (d) a summary of law and policy related to seclusion, (e) a summary of research on seclusion, (f) a declaration of principles, and (g) recommendations regarding the elimination of seclusion in educational settings. A parallel document provides recommendations related to the use of physical restraint procedures in educational settings, which is often associated with the use of seclusion procedures.